Recent Trends in Networks and Communications International Conferences, NeCoM 2010, WiMoN 2010, WeST 2010, Chennai, India, July 23-25, 2010. Proceedings - Meghanathan, Natarajan.; Boumerdassi, Selma.; Chaki, Nabendu.; Nagamalai, Dhinaharan. (Communications in Computer and Information Science,, 2010)
This book constitutes the proceedings of the Second International Conference on Networks and Communications, NeCoM 2010, the Second International Conference on Wireless and Mobile Networks,WiMoN 2010, and the Second International Conference on Web and Semantic Technology, WeST 2010, held in Chennai, India, in July 2010.